Pertumbuhan Bibit Tanaman Kelor (Moringa oleifera Lam.) Pada Beberapa Macam Media Organik dengan Teknik Pembibitan Tidak Langsung - Rasmani Rasmani; I Gusti Made Arya Parwata; Bambang Budi Santoso (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2018)
The experimental research is aimed to find out the kind of nursery organic media for better growth of drumstick seedling. It was implemented in January-April 2017 in the nursery field in Dasan Agung, Mataram. The treatments studied were kinds of nursery media including soil media, mixture of soil-sawdust, mixture of soil-cocopeat, mixture of soil-crushed corncobs, mixture of soil-bamboo leaf litter. The experiment design was arranged in a Completely Randomized Design with 5 replications and each content of 5 serial experiment units. The result shows that the kind of seedling media significantly affected the growth to Moringa seedling growth. The soil-cocopeat mixture medium, soil-crushed corn cobs, and soil-bamboo leaf litter were the best medium and more suitable for drumstick seedling compared to soil media and soil-sawdust mixture media